Modelling the Plastic Flow of Composite Materials in the Extrusion Process - Śliwa, R.E.; Mishuris, G.S. (Engineering Transactions, 1997)
The paper deals with an attempt of modelling the plastic flow of composed material based on the experimental results of co-extrusion of various materials. A modified mathematical description of the plastic flow in the extrusion of the bimetallic composite has been proposed. Boundaries of the plastic zone are described by appropriate functions adapted according to special choice of the proposed parameters. The flow field, the grid distortion and strain rate distribution have been approximated taking into account information on the plastic zone boundaries and their form. Different modes of simultaneous plastic deformation of dissimilar metals which are generally different from a mono-metal deformation are presented. Excellent agreement between the analytical and the experimental results of the plastic flow of composite has been found.